Shimmering images : trans cinema, embodiment, and the aesthetics of change - Steinbock, Eliza, 1980- (Duke University Press, 2019)
Eliza Steinbock traces how cinema offers alternative ways to understand gender transitions through a specific aesthetics of change, thereby opening up new means to understand transgender ontologies and epistemologies.